Upaya Guru PPKn dalam Penanaman Nilai-nilai Pendidikan Antikorupsi pada Siswa SMP IT As-Syifa - Hardiansyah, Muhammad Agus; Samsiah, Ami (IJTIMAIYA: Journal of Social Science and Teaching, 2023)
The study conducted in this article aims to know the teacher's efforts and elements in schools in instilling anti-corruption values at SMP AS-Syifa in advantage of anti-corruption values taught to citizenship education (PPKN). The method used in this research is descriptive qualitative research method. The culture of corruption is familiar in Indonesia therefore the importance of planting anti-corruption values. Anti-Corruption Culture is duly taught in learning. The role of teachers at schools not only teaches learning materials, but rather forming the personality of learners to have a concern, honesty, responsibility, discipline, simplicity, independence, and hard work that teaches at school. Not only limited through the role of teachers alone planting anti-corruption values is realized but many aspects that can support it can run well that is through the elements in school. Planting of anti-corruption values can be implanted to learners with various things to create a tanned generation of laws and rules. But the reality of schools not many teaches that indicator of good anticorruption in the elementary level to high school level. The leader of the educator, especially the teacher of the Citizenship Education Studies (PPKN) is essential in realizing the anti-corruption generation in the education environment. This is done to create critical learners and are oriented to the application of anti-corruption values in everyday life.